The Effectiveness Of Cultural Literacy Based BIPA Course Teaching Materials To Improve Students' Indonesian Language Proficiency - Nyayu Masnun Arief; Ramadan Lazuardi, Dian; Istiyah Yulianisah; Annisa Hidayati (Jurnal Scientia, 2024)
This research aims to determine the effectiveness of cultural literacy-based teaching materials for the Indonesian Language for Foreign Speakers (BIPA) course to improve students' Indonesian language proficiency. The research method used was an experiment with a pretest-posttest design with control group research design. Data collection uses interviews and tests. The research population is students of the Indonesian Language and Literature Education Study Program, semester VI of the 2024/2025 academic year who are taking BIPA subjects. The samples in the research were classes A and B. Research sampling was carried out using the intact group technique which resulted in class A as the experimental class and class B as the control class. The data analysis technique to determine the effectiveness of cultural literacy-based teaching materials for the Indonesian Foreign Speakers (BIPA) course to improve students' Indonesian language proficiency is carried out by analyzing pretest and posttest class learning outcomes using N-gain scores. Next, to determine the increase in Indonesian language proficiency of students in the control and experimental classes, a t-test was carried out using the SPSS program. The results of the research show that the teaching materials for the Indonesian Language for Foreign Speakers (BIPA) course based on cultural literacy to improve students' Indonesian language proficiency based on the n-gain score and n-gain score percent are effective to use. Based on the independent samples test output table, it is known that the Sig. (2-tailed) is 0.000 < 0.05, thus there is a significant difference in effectiveness in the control and experimental classes after using cultural literacy-based Indonesian Language for Foreign Speakers (BIPA) teaching materials to improve students' Indonesian language proficiency. So it can be concluded that students' Indonesian language proficiency increases after using cultural literacy-based Indonesian Language for Foreign Speakers (BIPA) teaching materials.